Frequent design concepts for conveying cultural identity toward accommodation architecture in Chiang Mai heritage district, Thailand - Chonnipa Kanchaikham; Masato Takagi (Journal of Asian Architecture and Building Engineering, 2024)
The Chiang Mai heritage district is widely recognized as a prime location for the hospitality industry’s cultural tourism sector. Within this area, accommodations diversely express cultural identity through architecture as their selling points. This study aims to explore the frequent design concepts employed by architects to convey cultural identities through recognized architecture. It focuses on eight accommodation architectures situated in the heritage district of Chiang Mai City. The research delves into the architects’ considerations during the design process. Data were collected through document reviews and architects’ interviews. The examination tested 60 design concepts, consisting of three categories: concrete, abstract, and nature-climate condition category. Seven concept groups resulted from two analysis methods of comparison and association rule. The findings reveal five key conveying concerns include 1) Climate adaptation and sustainability 2) Context connection 3) Traditional architectural perception 4) Integration of nature, local life, and social interaction 5) View of indoor green spaces. The research findings serve as a guide for architects aiming to create cultural accommodation experiences within Chiang Mai’s heritage area, ensuring appropriate representations of the city’s rich cultural heritage.